2015
DOI: 10.1159/000431360
|View full text |Cite
|
Sign up to set email alerts
|

Atopy and Asthma in Migrants: The Function of Parasites

Abstract: Migration studies have shown that environmental factors in more developed and industrialized countries facilitate atopy and asthma in a time-dependent manner and are affected by age at immigration. Levels of immunoglobulin E are higher in immigrants than in the local population and gradually decrease to the levels of the general population. Parasitic infestation may function in the prevention and pathogenesis of atopic conditions in immigrants from developing countries. Helminths are associated with a reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…In the late 1980s, it was suggested that childhood infections protect against allergies (Strachan 1989). While this has later been shown to be largely incorrect (Bloomfield et al 2016), increased hygiene, improved sanitation, and medical preventive care have led to reduced human infection by helminth parasites, which is considered to be one of the key reasons behind the allergy epidemic (Yazdanbakhsh et al 2002, Rottem et al 2015, Spencer & Zuk 2016. However, recent evidence suggest that the role of parasites is not independent of gut bacteria (Zaiss et al 2015).…”
Section: Ilkka Hanski: the Legacy Of A Multifaceted Ecologistmentioning
confidence: 99%
“…In the late 1980s, it was suggested that childhood infections protect against allergies (Strachan 1989). While this has later been shown to be largely incorrect (Bloomfield et al 2016), increased hygiene, improved sanitation, and medical preventive care have led to reduced human infection by helminth parasites, which is considered to be one of the key reasons behind the allergy epidemic (Yazdanbakhsh et al 2002, Rottem et al 2015, Spencer & Zuk 2016. However, recent evidence suggest that the role of parasites is not independent of gut bacteria (Zaiss et al 2015).…”
Section: Ilkka Hanski: the Legacy Of A Multifaceted Ecologistmentioning
confidence: 99%
“…International adoption involves not only exposure to a new macroenvironment, but it also implies significant socioeconomic and cultural changes, such as housing, diet and access to medical services [ 11 ]. A history of admission to unsuitable environments (orphanage, shelter, children’s home or other institution) at a young age, bringing about lack of stimulation, nutritional deficiencies and poor hygiene may influence the physical and mental health of children, making them individuals requiring special care [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that 56.5% of children exceeded normal age-adapted values for IgE and 31.3% of them were diagnosed with a parasitic infection. As numerous outbreaks in institutionalized settings have been reported, it is not surprising that intestinal protozoa are frequently identified on routine screening of international adoptees [ 11 , 28 30 ]. In a 2005 study, Murray identified that intestinal parasites are common in international adoptees children, with a prevalence of 14% to 33%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations